The Extracellular Signal-Regulated Kinase Cascade Is Required for NMDA Receptor-Independent LTP in Area CA1 But Not Area CA3 of the Hippocampus - Kanterewicz, Beatriz I. (J Neurosci, 2000)
Activation of extracellular signal-regulated kinase (ERK) has been shown to be necessary for NMDA receptor-dependent long-term potentiation (LTP). We studied the role of ERK in three forms of NMDA receptor-independent LTP: LTP induced by very high-frequency stimulation (200 Hz-LTP), LTP induced by the K(+)channel blocker tetraethylammonium (TEA) (TEA-LTP), and mossy fiber (MF) LTP (MF-LTP). We found that ERK was activated in area CA1 after the induction of both 200 Hz-LTP and TEA-LTP and that this activation required the influx of Ca(2+) through voltage-gated Ca(2+) channels. Inhibition of the ERK signaling cascade with either PD 098059 or U0126 prevented the induction of both 200 Hz-LTP and TEA-LTP in area CA1. In contrast, neither PD 098059 nor U0126 prevented MF-LTP in area CA3 induced by either brief or long trains of high-frequency stimulation. U0126 also did not prevent forskolin-induced potentiation in area CA3. However, incubation of slices with forskolin, an activator of the cAMP-dependent protein kinase (PKA) cascade, did result in increases in active ERK and cAMP response element-binding protein (CREB) phosphorylation in area CA3. The forskolin-induced increase in active ERK was inhibited by U0126, whereas the increase in CREB phosphorylation was not, which suggests that in area CA3 the PKA cascade is not coupled to CREB phosphorylation via ERK. Overall, our observations indicate that activation of the ERK signaling cascade is necessary for NMDA receptor-independent LTP in area CA1 but not in area CA3 and suggest a divergence in the signaling cascades underlying NMDA receptor-independent LTP in these hippocampal subregions.